Legal Protection of Women's and Children's Rights in Religious Court Divorce Decisions - Hidayatur Rahman; Sri Lum'atus Sa'adah; Busriyanti (Syntax Corporation Indonesia, 2023)
Protection of women and children in the context of marriage, not only during marriage but after divorce. Protection of women and children after divorce has gained legality since the existence of SEMA No. 3 of 2018. Since the birth of SEMA, women have been able to claim their rights even through divorce, as was the case in the Jember Religious Court decision. This research was conducted to find out 1) How the Judges of the Jember Religious Court considered the post-SEMA no. 3 of 2018. 2) What is the legal protection for women and children in the Jember Religious Court decision after SEMA No. 3 of 2018. The results of this research show 1) The judge's considerations in the decision to clarify post-SEMA No. 3 of 2018 by looking at the reasons/arguments that can be proven to be legal facts. There are three aspects of consideration, namely the first, the philosophical aspect, namely, the juridical aspect, namely and sociological considerations. 2) A form of legal protection for the rights of women and children in the divorce decision at the Jember religious court's ruling, namely that the wife gets mut'ah, madhiyah and living expenses during the iddah, legal protection for children is the right to get decent living expenses. This is as stipulated in SEMA No. 3 of 2018 All these decisions contain three legal ideals, namely justice, certainty and legal benefits.